PENGARUH IKLIM KERJA TERHADAP SEMANGAT KERJA KARYAWAN (KASUS BAGIAN PRODUKSI PENGOLAHAN CPO PT. ASMJ KUANSING - Riska Pafera Multi; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Abstract: This research goes from from the problems of the low productivity of theemployee section of the production processing of CPO at PT. ASMJ Kuansing,indicated by is not the achievement of a target production of set and the presenceof disiplinan employees of ditetap company work rules. As for the purpose of thisresearch is to know the working Climate and employee morale as well asinfluence the granting of Work Climate to increased employee morale theProduction processing of CPO in PT.ASMJ Kuansing. This research analyzes thedata by using a descriptive quantitative analysis and to answer hypotheses havebeen proposed to do statistical analysis using simple linear regression. Results ofthe study concluded that the granting of incentives overall judged to have goodand overall employee morale was judged good enough. Based on the results ofdata analysis through statistical analysis, it can be noted that the independentvariables (climate) have an influence on the dependent variables are (employeemorale). The independent variables (climate work) give a positive and significanteffect on the dependent variable (employee morale), so that when more freevariables are fixed then it will give rise to an increase of the variable is bound.Keywords: The Working Climate, employee, morale